2013
DOI: 10.4103/0972-124x.124493
|View full text |Cite
|
Sign up to set email alerts
|

Rotary instruments in the treatment of chronic periodontitis: A randomized clinical trial

Abstract: Background:The study aimed at comparing the effectiveness of rotary instruments with hand instruments in non-surgical treatment of chronic periodontitis.Materials and Methods:Thirty-eight patients with chronic periodontitis, enrolled to this randomized, controlled clinical trial, were divided into two groups. Patients in the control group received scaling and root planing with hand instruments, whereas patients in the test group received treatment with rotary instruments. Clinical assessment by plaque index, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Dahiya et al, showed how the use of rotary instruments in chronic periodontal disease treatment gives comparable results with the traditional approach of scaling and root planning [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dahiya et al, showed how the use of rotary instruments in chronic periodontal disease treatment gives comparable results with the traditional approach of scaling and root planning [16].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome these difficulties, associated with hand instrumentation and ultrasonic scalers, rotary instrument was introduced in periodontal treatment for scaling and root planning [15,16].…”
Section: Introductionmentioning
confidence: 99%